Review Biodegradation a Real tool in environmental cleaning - Duha Bahaa Mohammed Al Fayaad; Yaaroub Faleh Al Fatlawy (Zien Journals, 2022)
This paragraph explains there are several bioremediation techniques that use a range of microorganisms to treat contaminated settings. Biodegradation has been used in the last 20 years as a tool for environmental cleanup. By using their extracellular enzymes to speed up the bioremediation process, bacteria, algae, yeast, and fungi can all be utilized in the remediation of polluted environments. Due to its exceptional capacity to adapt to a variety of pollutants as well as its ability to bio-absorb and bio-convert the pollutants into less harmful products than the parental recalcitrant pollutants, fungi have attracted a lot of interest in their ability to decontaminate polluted environments.
Keywords: Filamentous fungi; biodegradation